Parental Support and School Environment as Determinants of Obesity Risk among School-Aged Children: A Cross-Sectional Study - Nurharlinah, Nurharlinah; Athiutama, Ari; Karyatin, Karyatin; Herdiani, Rini (Journal of Applied Nursing and Health, 2026)
Background: Childhood obesity is an increasing public health concern among school-aged children, particularly in low- and middle-income countries (LMICs). While parental support and the school environment are recognized as important determinants, evidence comparing their relative influence within a socio-ecological framework remains limited. This study aimed to examine the association between parental support, the school environment, and obesity risk among school-aged children in Indonesia. Methods: A cross-sectional study was conducted on 120 children aged 7–12 years using a purposive sampling method. Data were collected using a validated parental support questionnaire, school environment assessment instrument, and anthropometric measurements to determine the body mass index (BMI) for age. Associations were analyzed using the chi-square tests and multivariable logistic regression. This study was conducted in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. Results: Both parental support and school environment were significantly associated with obesity risk. Children with low parental support had higher odds of obesity (OR = 2.50; 95% CI: 1.20–5.10), whereas those exposed to less healthy school environments had even higher odds of obesity (OR = 2.80; 95% CI: 1.35–5.80). Among the examined factors, the school environment demonstrated the strongest independent association with the risk of obesity. Conclusion: Parental support and the school environment are important determinants of obesity risk among school-aged children; however, school-level factors appear to play a more dominant role in this regard. These findings highlight schools as a critical entry point for childhood obesity prevention within a socio-ecological framework, particularly in LMIC.